The effect of probiotic supplementation on performance, inflammatory markers and gastro-intestinal symptoms in elite road cyclists - Schreiber, C.; Tamir, S.; Golan, R.; Weinstein, A.; Weinstein, Y. (Journal of the International Society of Sports Nutrition, 2021)
Background: Elite athletes may suffer from impaired immune function and gastro-intestinal (GI) symptoms, which may affect their health and may impede their performance. These symptoms may be reduced by multi-strain probiotic supplementation. Therefore, the aim of the current study is to examine the effects of probiotic supplementation on aerobic fitness characteristics, inflammatory markers and incidence and severity of GI symptoms in elite cyclists. Methods: Twenty-seven male cyclists, ranked elite or category 1 level competitions, were randomly assigned to a multi-strain probiotic-supplemented group (E, n = 11) or placebo group (C, n = 16). All participants visited the laboratory at the beginning of the study and following 90 d of supplementation/placebo. Prior to testing, all participants completed a GI symptoms questionnaire and underwent physical and medical examination, and anthropometric measurements. Venous blood was drawn for inflammatory markers analysis. The cyclists then underwent maximal oxygen consumption (VO2max) test and time-to-fatigue (TTF) test at 85 % of maximal power, 3 h following the VO2max test. All testing procedures were repeated after 90 d of probiotic / placebo treatment (double blind design). Results: Lower incidence of nausea, belching, and vomiting (P < 0.05) at rest, and decreased incidence of GI symptoms during training were found in E group vs. C Group, respectively (?GI -0.27 ± 0.47 % vs. 0.08 ± 0.29 %, P = 0.03), no significant changes were observed in the incidence of total overall GI symptoms (?GI -5.6 ± 14.7 % vs. 2.6 ± 11.6 %, P = 0.602) Mean rate of perceived exertion (RPE) values during the TTF were lower in E group (?RPE: -0.3 ± 0.9 vs. 0.8 ± 1.5, P = 0.04). No significant changes were measured between and within groups in VO2max and TTF values, mean levels of C-reactive protein (CRP), IL-6-and tumor necrosis factor alpha (TNFa) values following treatment. Conclusions: Probiotics supplementation may have beneficial effects on GI symptoms in elite cyclists. Future studies, using higher doses and during different training seasons, might help understanding the effects of probiotic supplementation on elite athletes` health and performance.